Reporting of HIV-infected pregnant women: estimates from a Brazilian study - Rosa Maria Soares Madeira Domingues; Valéria Saraceni; Maria do Carmo Leal (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: To estimate the coverage of the reporting of cases of HIV-infected pregnant women, to estimate the increase in the coverage of the reporting with the routine search of data in other Brazilian health information systems, and to identify missed opportunities for identification of HIV-infected pregnant women in Brazilian maternity hospitals. METHODS: This is a descriptive study on the linkage of Brazilian databases with primary data from the "Nascer no Brasil" study and secondary database collection from national health information systems. The "Nascer no Brasil" is a national-based study carried out in 2011-2012 with 23,894 pregnant women, which identified HIV-infected pregnant women using prenatal and medical records. We searched for cases of HIV-infected pregnant women identified in the "Nascer no Brasil" study in the Information System of Notifiable Diseases, the Control System for Laboratory Tests of the National CD4+/CD8+ Lymphocyte Count and HIV Viral Load Network, and the Logistics Control System for Medications. We used the OpenRecLink software for the linkage of databases. We estimated the notification coverage, with the respective confidence interval, of the evaluated Brazilian health information systems. RESULTS: We estimated the coverage of the reporting of HIV-infected pregnant women in the Information System of Notifiable Diseases as 57.1% (95%CI 42.9-70.2), and we located 89.3% of the HIV-infected pregnant women (95%CI 81.2-94.2) in some of the Brazilian health information systems researched. The search in other national health information systems would result in an increase of 57.1% of the reported cases. We identified no missed opportunities for the diagnosis of HIV+ in pregnant women in the maternity hospitals evaluated by the "Nascer no Brasil" study. CONCLUSIONS: The routine search for information in other Brazilian health information systems, a procedure carried out by the Ministry of Health for cases of AIDS in adults and children, should be adopted for cases of HIV in pregnancy.